Classification of Ni Levels for Determination Cut-Off Grade in Region X - Nurliah Jafar; Hendra Wahid; Sri Widodo (CV Insight Publisher, 2022)
The need for ore with levels above 1.8% presents the author's initiative to conduct research to produce ore products with the required levels. The aim is to find out the lowest grade of ore that can be mined and used as a cut-off grade in area x. The research method used is the blending method. Some of the data needed include the drill point coordinates, the borehole's depth, the borehole, the slope of the borehole, lithology, and the value of Ni content. The distribution of nickel in the x region is dominated by ore which has a grade of 1 to 2% with a total volume of 140,100 Bcm, and there is a small amount of nickel that has a rate above 2% with an importance of 15,650 Bcm. The mining sequence has been divided into three to three stages, where the tonnage obtained from each location is 8,9937 tons, 442361 tons, and 100,554 tons. The simulation of blending steps was carried out starting from the classification of nickel with the highest grade, namely nickel with the lowest rate of 1.8% with an average rise of 2.07%, to the last stage, which produces a middle grade of 1.9%, namely in the classification of nickel with rates above 1.6 %. From the results of the blending simulation that has been carried out, it can be concluded that the lowest grade that can be used as a cut-off grade in area x is ore with a Ni content of 1.6%.